Exploring the influence of power dynamics on collaborative governance in the Thukela Catchment - Dunyana, Philisa (Rhodes University, Faculty of Science, Department of Environmental Science)
South Africa is a water-scarce country with unequally distributed water. This dilemma has been brought about by insufficient water supply and governance fragmentation, among other drivers. The democratic national water policies (National Water Act No. 36 of 1998) intend to foster collaborative water governance (CWG), where stakeholders within catchments must come together to learn and share decision-making responsibility through collaborative platforms that should ensure the sustainability and equitable distribution of water resources. Still, CWG is not functioning well in most parts of the country, partly due to power dynamics that compromise dynamics on collaborative governance processes and outcomes in the Upper Thukela Catchment (UTC). It did this by identifying the roles of stakeholders, looking into the nature of power dynamics among stakeholders and how these affect collaborative processes, and by examining how power dynamics interact with resources and mechanisms to influence collaborative governance outcomes. The research used two interrelated conceptual frameworks (Franks and Cleaver (2007) and the 4Rs framework (Mayers, 2005)) to explore power dynamics. The study was conducted through qualitative research using a case study approach, which consists of data collection methods such as in-depth semi-structured interviews, document review, direct observation and participant observation. The 4Rs framework highlighted the insufficient involvement of critical stakeholders in water governance, specifically those from the public sector with water management and governance authority rights. The analysis also exposed conflicting relationships among stakeholders involved in water governance, mostly stemming from some public sector stakeholders evading roles and responsibilities, a lack of trust, and limited access to information. These factors contribute to challenges and tensions within the water governance landscape in the UTC. The research also showed that the presence of different political parties in the water governance and management space seems to be the primary roots of the power dynamics that affect the processes of water governance and management. Political parties contesting power over the same communities led to conflict, corruption, competition, negligence, and sabotage. These challenges impact operational flow, service delivery, sense of urgency, and decisionmaking. Thus, the nature of power dynamics in collaborative governance processes further exposed the underlying issue of limited statehood. Application of the Franks and Cleaver (2007) framework revealed that through their influence on power dynamics, resources and mechanisms of access affect livelihoods and catchment outcomes. The study contributes to the body of knowledge on the influence of power dynamics on collaborative governance and provides recommendations for further studies to improve collaborative water governance. It highlights the complex interplay between power dynamics, stakeholder participation, and water governance processes in the UTC. To improve collaborative water governance, it is crucial to address limited stakeholder participation, mitigate the negative influence of political parties, and meaningfully empower local communities.
Keywords: Stakeholder participation; Watershed management -- South Africa Tugela River Watershed; Water security -- South Africa; Collaborative governance; Decision making; Conflict management